The Potential of Beneficial Microbes for Sustainable Alternative Approaches to Control Phytopathogenic Diseases - Ramadan Bakr; Ali Abdelmoteleb; Vianey Mendez-Trujillo; Daniel Gonzalez-Mendoza; Omar Hewedy (Microbiology Research)
Sustainable agricultural practices are essential for eradicating global hunger, especially in light of the growing world population. Utilizing natural antagonists, such as fungi and bacteria, to combat plant diseases, rather than relying solely on synthetic chemical pesticides, which pose significant risks to the environment and human health, is known as biocontrol. Microbial biological control agents (MBCAs) have proven effective against phytopathogens and are increasingly embraced in agricultural practices. MBCAs possess several beneficial traits, including antagonistic potential, rhizosphere competence, and the ability to produce lytic enzymes, antibiotics, and toxins. These biocontrol mechanisms directly target soil-borne pathogens or indirectly stimulate a plant-mediated resistance response. The effectiveness of MBCAs in managing plant diseases depends on various mechanisms, such as hyperparasitism, antibiosis, competition for nutrients or space, disruption of quorum-sensing signals, production of siderophores, generation of cell wall-degrading enzymes, and the induction and priming of plant resistance. Formulating effective biopesticides requires optimal conditions, including selecting effective strains, considering biosafety, appropriate storage methods, and ensuring a prolonged shelf life. Therefore, formulation is crucial in developing pesticide products, particularly concerning efficacy and production costs. However, several challenges must be addressed to ensure the successful application of biological control, including the shelf life of biopesticides, slower efficacy in pest management, inadequate awareness and understanding of biocontrol methods, regulatory registration for commercialization, and suitable agricultural applications. This review clarifies the principles of plant disease biocontrol, highlighting the mechanisms of action and functionality of MBCAs in biocontrol activities, the formulation of biopesticides derived from microorganisms, and the challenges and barriers associated with the development, registration, commercialization, and application of biopesticides.